B15 Innate transcriptional dysregulation is associated with proinflammatory pathway activation in huntington's disease myeloid cells. (13th September 2016) - Andre, Ralph; Miller, James RC; Lo, Kitty K; Hensman Moss, Davina J; Träger, Ulrike; Stone, Timothy C; McErlean, Peter; Jones, Lesley; Holmans, Peter; Lavender, Paul; Plagnol, Vincent; Tabrizi, Sarah J
Abstract : Background: While the central nervous system is considered to be the primary site of Huntington's disease (HD) pathology, patients exhibit a wide range of peripheral abnormalities. Indeed, there is much interest in the systemic innate immune system as a modifier of disease progression, with HD myeloid cells exhibiting numerous functional abnormalities, but the molecular mechanisms underpinning these changes remain only partially understood. Aim: To investigate alterations in transcriptional regulation that are associated with HD myeloid cell hyper-reactivity. Methods: RNA deep-sequencing was performed for whole transcriptome analysis of primary monocytes isolated from HD patients and control subjects cultured with and without a proinflammatory stimulus and various bioinformatic analyses were carried out. ChIP-seq was undertaken to identify changes in histone modifications or transcription factor binding that are associated with altered transcription. Results: Significant transcriptional differences in HD monocytes in their basal, unstimulated state were observed, including elevated expression of genes encoding proinflammatory cytokines. That such differences are observed under basal conditions contrasts with previous studies that have required stimulation to elicit phenotypic abnormalities. Pathway analysis of differentially expressed genes reveals an enrichment of genes associated with innate immunity and the inflammatory response, while analysis of upstream regulators suggests that abnormal activation of particular intracellular signalling pathways plays a major causative role in mediating this transcriptional dysregulation. The precise mechanism by which mutant huntingtin exerts these effects may reside in particular histone modifications and/or altered transcription factor binding to increase the expression of specific sets of genes. Conclusions: HD myeloid cells are intrinsically abnormal, with a proinflammatory phenotype in the absence of stimulation that is consistent with a priming effect of mutant huntingtin such that an exaggerated inflammatory response is produced when a stimulus is encountered. This is associated with transcriptional dysregulation, which may be a key mechanism causing innate immune dysfunction in Huntington's disease.